How would the COVID-19 pandemic reshape retail real estate and high streets through acceleration of E-commerce and digitalization? - Anupam Nanda; Yishuang Xu; Fangchen Zhang (Journal of Urban Management, 2021)
This paper aims to explore the impact of the COVID-19 pandemic on retail real estate and high street landscape through acceleration of e-commerce and digitalization. The retail business have been evolving over the past several decades, accentuated by the evolution and development of digital technologies. Almost all parts of the world have witnessed the changes in consumer behavior, the nature of retail, and reshaping of the high street landscape due to the e-commerce revolution and continued expansion. Especially due to the COVID-19 pandemic, the retail platforms powered by digital technology had to be adapted quickly, and it is expected to continue to support this change as consumers and retailers adjust to new normalities. Moreover, retail real estate is intricately linked with the retail sector dynamics. While lockdown and social distance rules have devastating impacts on "traditional" retail property sector, it may accelerate the evolution process of multi-channel retail and the channel integration role of physical stores and thus, bring in transformations in urban-retail landscape. It is not necessarily leading to an end of high street stores, but it may have a significant impact on retail real estate business. There remains a lack of understanding of how these changes may pan out with a rigorous academic investigation. To close this knowledge gap, we analyze both the strategy event data of a range of UK retailers as well as the insights from interviews with retail asset manager and landlords using a mixed-method approach. The findings indicate an urgent need for physical shops to reposition the functions of their multi-channel business. Our analysis provide significant insights and highlight several implications for retailers, landlords and, also policy-making units dealing with urban regeneration and local economic development in the post-COVID-19 world.
Keywords: 710; Retail real estate; Digitalization; E-commerce; COVID-19